Reaction site diversity in the reactions of titanium hydrazides with organic nitriles, isonitriles and isocyanates: Ti=N(α) cycloaddition, Ti=N(α) insertion and N(α) -N(β) bond cleavage. - Schofield, A; Nova, A; Selby, J; Schwarz, A; Clot, E; Mountford, P (2011)
We report a range of new transformations of the diamide-amine supported Ti=NNPh(2) functional group with a variety of unsaturated substrates, along with DFT studies of the key mechanisms. Reaction of [Ti(N(2) N(py) )(NNPh(2) )(py)] (4, N(2) N(py) =(2-NC(5) H(4) )CMe(CH(2) NSiMe(3) )(2) ; py=pyridine) with MeCN gave the dimeric species [Ti(2) (N(2) N(py) )(2) {μ-NC(Me)(NNPh(2) )}(2) ] through a [2+2] cycloaddition process. Reaction of 4 or [Ti(N(2) N(Me) )(NNPh(2) )(py)] (5, N(2) N(Me) =MeN(CH(2) CH(2) NSiMe(3) )(2) ) with fluorinated benzonitriles gave the terminal hydrazonamide complexes [Ti(N(2) N(R) ){NC(Ar F x)NNPh(2) }(py)] (R=py or Me; Ar F x=2,6-C(6) H(3) F(2) or C(6) F(5) ). DFT studies showed that this proceeds through an overall [2+2] cycloaddition-reverse cycloaddition, resulting in net insertion of Ar F xCN into the Ti=N(α) bonds of the respective hydrazides. Reaction of 4 with a mixture of MeCN and PhCCMe gave the metallacycle [Ti(N(2) N(py) ){NC(Me)C(Ph)C(Me)NNPh(2) }] by sequential coupling of Ti=NNPh(2) with PhCCMe and then MeCN. A related product, [Ti(N(2) N(py) ){NC(Me)C(Ar(F) )C(H)NNPh(2) }], was formed by insertion of MeCN into the Ti-C bond of the isolated azatitanacyclobutene [Ti(N(2) N(py) ){N(NPh(2) )C(H)C(Ar(F) )}] (Ar(F) =3-C(6) H(4) F). Reaction of 4 with two equivalents of B(Ar F 5)(3) (Ar F 5=C(6) F(5) ) formed the zwitterionic borate [Ti(N(2) N(py) ){η(2) -N(NPh(2) )B(Ar F 5)(3) }] by electrophilic attack at N(α) . Compounds 4 and 5 reacted with tBuNC and/or XylNC (Xyl=2,6-C(6) H(3) Me(2) ) to give the N(α)-N(β) bond cleavage products, [Ti(N(2) N(R) )(NCNR')(NPh(2) )] (R=py or Me; R'=tBu or Xyl), containing metallated carbodiimide ligands. DFT studies of these reactions found an initial addition of RNC across Ti=N(α) followed by N(β) coordination, and finally complete N(α) transfer from the NNPh(2) to the RNC fragment. Reaction of 5 with Ar'NCE (E=O, S, Se; Ar'=2,6-C(6) H(3) iPr(2) ) gave the [2+2] cycloaddition products [Ti(N(2) N(Me) ){N(NPh(2) )C(NAr')O}(py)] and [Ti(N(2) N(Me) ){N(NPh(2) )C(NAr')E}] (E=S or Se), which did not undergo further transformation of the Ti-N-NPh(2) moiety.